Pengembangan Krim Tabir Surya Herbal Menggunakan Clitoria ternatea dan Aloe vera: Formulasi, Penilaian Kualitas, dan Efikasi In Vivo - Indarto Indarto; Sri Purwanti Nasution; Ajeng Dwi Anita Suci; Hawa Purnama Celala Ary Cane (Jurnal Farmasi Indonesia, 2024)
Increased awareness of the adverse effects of ultraviolet (UV) radiation has led to the development of sunscreen formulations that utilize natural ingredients for enhanced skin protection. This study aimed to develop and evaluate a herbal sunscreen cream combining extracts from Clitoria ternatea and Aloe vera for their UV protection efficacy using an in vivo murine model. The experimental design included the formulation of creams with varying concentrations of the active ingredients, followed by assessments of homogeneity, spreadability, adhesiveness, viscosity, pH, and hedonic qualities. In vivo sunscreen activity was tested on mice, measuring the Sun Protection Factor (SPF). Results showed that creams containing higher concentrations of the extracts (F4) had significantly increased SPF values 35, indicating effective UV protection. The creams also demonstrated good homogeneity, appropriate pH levels, and were well-received in hedonic tests. The study concludes that the combination of Clitoria ternatea and Aloe vera extracts can serve as a potent natural alternative to synthetic sunscreen agents.